Hospital-based descriptive epidemiology of intracranial meningiomas in Palestine: A retrospective study from a major referral center (2018–2023) - Mohammad Abuawad; Ahmad Rjoub; Yazan Dumaidi; Motaz Daraghma; Mohammad A. Nour; Wafaa Abu Zahra; Noor Issa; Ahmed Daqour; Abdulsalam Alkaiyat (PLoS ONE, 2026)
Objective Intracranial meningioma is the most common type of primary brain tumor globally. This study aimed to determine the epidemiological characteristics of intracranial meningioma in Palestine from 2018 to 2023. Methods We conducted a retrospective hospital-based descriptive study of radiologically and histologically confirmed intracranial meningiomas treated or referred to Al-Makassed Hospital, the main neurosurgical referral center in Palestine, from September 7 th , 2023, to November 16 th , 2023. Patients’ reports were the main source for data collection. Histopathological types of meningioma were coded according to the 2016 WHO Classification for CNS tumors. The incidence rates of intracranial meningiomas were hospital-based referral-center minimum estimates, calculated based on the total population size. Results A total of 204 cases of intracranial meningioma were identified. The mean age at diagnosis was 51.12 years (±13.96). The estimated minimum hospital-based crude incidence rate was 0.65 per 100,000 person-years (95% CI: 0.56–0.75), with a higher incidence in females than in males (0.88 vs 0.43, (0.88 vs 0.43 per 100,000 person-years, IRR = 2.07 [95% CI: 1.53–2.81]; p = 0.003). Grade I meningiomas were the most common, accounting for 81.4%. Grade II and III meningiomas were more common in males. Focal Neurological Symptoms (39.7%) were the most prevalent presenting symptoms. Intracranial meningiomas were most often managed with surgical resection alone (96.6%). Conclusion This study provided insights into the epidemiological characteristics of meningioma in Palestine. These findings represent hospital-based minimum estimates and are not directly comparable to population-based registry data. Meningiomas were more common in females, while higher-grade meningiomas were more common in males. Further research is needed to ascertain the most common subtypes.